Enterprise Architecture Planning Pada Pemerintah Desa Lolong Dengan Zachman Framework - muda, rosalia; Saitakela, Mardhalia (Universitas Multi Data Palembang, 2025)
The purpose of implementing E-Government in the village government environment is to realize an effective, efficient, open, and accountable government. E-government in Lolong Village at the internal level of government organizations has been implemented, as evidenced by the availability of information systems used by village officials. However, the system used only supports part of the business process activities. In the village, administrative bookkeeping services are still recorded on hard or paper, where data storage takes a long time and is less efficient. This research aims to make information system architecture planning using the Zachman Framework, which can provide recommendations for the development of a planned system to help each work unit in the Lolong Village government, so that data management can be integrated with efficiency. The expected result of this study is a Blueprint as structured guidance so that it can be used as a basis for developing a structured information system that is in accordance with the needs of the village government.